The Use of Local Wisdom-Based E-LKPD in Science and Social Studies Learning for Grade IV Students of Cluster V, Seririt District - Made Sutawan; I Gede Suwindia; Ni Nyoman Kurnia Wati (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study was conducted in response to a persistent gap in contextual and meaningful IPAS learning at the elementary level — one that, despite growing attention in the literature, has not been adequately addressed through systematic synthesis. The specific concern is whether electronic student worksheets grounded in local wisdom, particularly those carrying the values of Tri Kaya Parisudha, can be said to produce consistent, documentable effects on students' critical thinking and character development. Previous studies have addressed pieces of this question, but none have drawn them together with sufficient rigor. A Systematic Literature Review was therefore conducted, following the PRISMA protocol across four stages: identification, screening, eligibility, and inclusion. Source materials were drawn from accredited national journals and relevant scientific publications. Of 45 articles initially identified, 10 met the inclusion criteria and were subjected to descriptive qualitative analysis. The findings indicate that local wisdom-based electronic worksheets produced measurable gains in learning outcomes, motivation, active participation, and critical thinking. The incorporation of Tri Kaya Parisudha values — manacika, wacika, and kayika — also appeared to reinforce students' attitudinal development in ways that standard digital worksheets did not. Taken together, the evidence positions local wisdom-based electronic worksheets as a contextually grounded and educationally sound resource for IPAS instruction in elementary schools, one that serves cognitive and character goals simultaneously.